An epidemiological appraisal of the association between heart rate variability and particulate air pollution: a meta-analysis. Issue 15 (23rd May 2012) - Pieters, Nicky; Plusquin, Michelle; Cox, Bianca; Kicinski, Michal; Vangronsveld, Jaco; Nawrot, Tim S
Abstract : Objective: Studies on the association between short-term exposure to ambient air pollution and heart rate variability (HRV) suggest that particulate matter (PM) exposure is associated with reductions in measures of HRV, but there is heterogeneity in the nature and magnitude of this association between studies. The authors performed a meta-analysis to determine how consistent this association is. Data source: The authors searched the Pubmed citation database and Web of Knowledge to identify studies on HRV and PM. Study selection: Of the epidemiologic studies reviewed, 29 provided sufficient details to be considered. The meta-analysis included 18667 subjects recruited from the population in surveys, studies from patient groups, and from occupationally exposed groups. Data extraction: Two investigators read all papers and computerised all relevant information. Results: The authors computed pooled estimates from a random-effects model. In the combined studies, an increase of 10 μg/m 3 in PM2.5 was associated with significant reductions in the time-domain measurements, including low frequency (−1.66%, 95% CI −2.58% to −0.74%) and high frequency (−2.44%, 95% CI −3.76% to −1.12%) and in frequency-domain measurements, for SDNN (−0.12%, 95% CI −0.22% to −0.03%) and for rMSSD (−2.18%, 95% CI −3.33% to −1.03%). Funnel plots suggested that no publication bias was present and a sensitivity analysis confirmed the robustness of our combined estimates. Conclusion: The meta-analysis supports an inverse relationship between HRV, a marker for a worse cardiovascular prognosis, and particulate air pollution.